CREATING INTERACTIVE TEACHING LITERATURE IN THE ISPRING PROGRAM - Yusupova Shohida Botirboyevna; Ortiqov Bekzod Qadamboyevich; Qadirova Mohinur Iskandar qizi; Ko‘palov Jaxongir Palvannazir o‘g‘li (Web of Journals Publishing, 2024)
Currently, the breadth of use of mobile teaching aids is the need to create mobile teaching programs, didactic learning resources, teaching programs, courses and control tests. In view of these requirements, the ispringsuite8 program provides information on how to create an interactive educational resource.
Keywords: mobile banking, mobile internet, mobile commerce, mobile education, distance education, iSpringSuite8, smartphone, interactive learning resource, HTML5.